TRANSFORMATION OF BIJB KERTAJATI MAJALENGKA AS THE SELECTED LOGISTIC TRANSPORTATION OF WEST JAVA MARINE AND FISHERY INDUSTRY - Dian Prima Ayufita (Politeknik Bisnis Indonesia, 2023)
As an export and import gate, the West Java fisheries and marine industry did not select BIJB Kertajati Majalengka. There needs to be more communication from BIJB to West Java's marine and fisheries industry regarding cargo and BIJB facilities. The research aim is how to transform BIJB Kertajati Majalengka as logistics transportation for West Java's marine and fisheries industries that is carried out to understand the potential, opportunities, and strategy. Systems Thinking is created by qualitative analysis. This research used primary data through questionnaires, interviews, FGD, and secondary data through other information. Data analysis using selective coding. The result shows that West Java has the potential for the Marine and Fisheries Logistics Industry in West Java as a target for the BIJB approach. The potential for the fishery and marine industry in West Java is enormous, making BIJB's opportunities very large. The strategy that must be carried out are building approaches with overseas buyers; taking a political system with the government to make mandatory policies; conducting socialization; submitting to the West Java government to be able to provide subsidies or facilities for the West Java marine and fisheries industry using logistics transportation through BIJB Kertajati Majalengka.